Are smartphone buyers being rational? - Mulia, Dipa; Muchsin Saggaff Shihab (Dinasti International Journal of Digital Business Management, 2023)
This research is related to consumer behavior when purchasing a smartphone one of product that is closely related to technology. The purpose of this study is to determine marketing strategies by analyzing consumer behavior both rational aspect and emotional aspects. The independent variables represent rational aspect are technology, price perception, e-WoM, while emotional aspect represented by Emotion variable, and Trust is selected as a mediator variable of rational aspect. As the dependent variable is the intention to buy a smartphone. This research is a quantitative research, the sample used in this study was taken by purposive sampling method with the criteria of the respondent is smartphones users. The number of samples in this study is 338 respondents. The analysis used in the research uses structure equation modeling (SEM) to test the hypotheses in the proposed research model.